Reforma previdenciária – uma análise da proposta de emenda à constituição Nº 06/2019 e seu impacto sobre a vida do trabalhador - Freitas, Fernanda Rafaela Maia de (Universidade Federal Rural do Semi-Árido, 2019)
This paper analyzes the proposal to reform the brazilian social security system, starting with the recent PEC 06/2019, which rekindled the discussions on the topic in the national scenario. Bringing out a concern with its effects, which focus especially on the rights of the main beneficiary and maintainer of the Pension Plan, the employee. The social security system being a security for the worker regarding the future; whether in situations of retirement, illness, disability, among others; it is of essential importance to understand how the changes intended through the reform impact the coverage given to the social risks directly related to the employee, insured of the Social Security. It is also important to realize the actions of the Social Security as a mechanism to mitigate social inequalities, through welfare benefits, which in turn will also undergo important changes according to the proposed text. Analyze the main changes proposed by PEC 06/2019, which bring real impact on the working class and superficially perceive diverse solutions for the main foundation of the pension reform, the public deficit. Seeking with the study of the theme, not its overcoming; but from a new look and based on related studies; propose less harmful alternatives to workers' rights.
Artigo Acadêmico
Keywords: Reforma Previdenciária; PEC 06/2019; Impactos; Trabalhador; Social security reform; PEC 06/2019; Impacts; Employees; CIENCIAS SOCIAIS APLICADAS::DIREITO